In vitro study of antioxidant and antibacterial activities of Lactobacillus probiotic spp - Pourramezan, Z; Kasra Kermanshahi, R; Oloomi, M; Aliahmadi, A; Rezadoost, H (Folia microbiologica, 2018)
This study investigated the influence of aeration and minimal medium conditions on antioxidant and antibacterial activities of 21 probiotic Lactobacillus strains isolated from dairy products. The probiotic potential of the isolates was evaluated by pH and bile tolerance. Random amplified polymorphic DNA polymerase chain reaction (RAPD-PCR) was used to confirm the phenotypic identification of isolates. Antioxidant producer isolates were screened by resistance to reactive oxygen species (ROS). The antioxidant and antibacterial activities of extracellular materials after 48 h fermentation with antioxidative strains were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and broth microdilution assays, respectively. The results indicate that the antioxidant capacity of supernatants was increased by using of both minimal medium and agitation. The antibacterial activity was increased in minimal medium, but there has nearly no change in the antibacterial properties by using both agitation and minimal medium. The maximum antibacterial activity was observed during mid-exponential phase until the beginning of the early-stationary phase, but the maximum antioxidant activity was detected at the stationary growth phase. There is a significant relationship between antioxidant and antibacterial activities of the cell-free probiotic extracts, and their production rates are closely related to the fermentation type. The bioactive materials from probiotics could be extracted in a large amount at an appropriate time under a suitable condition.
Keywords: Lactobacillus; antibióza; probiotika; Probiotics; antioxidancia; antibakteriální látky; Fermentation; Antioxidants; Anti-Bacterial Agents; fermentace; Antibiosis